Next generation sequencing of lung adenocarcinoma subtypes with intestinal differentiation reveals distinct molecular signatures associated with histomorphology and therapeutic options. (December 2019) - Jurmeister, Philipp; Vollbrecht, Claudia; Behnke, Anke; Frost, Nikolaj; Arnold, Alexander; Treue, Denise; Rückert, Jens-Carsten; Neudecker, Jens; Schweizer, Leonille; Klauschen, Frederick; Horst, David; Hummel, Michael; et al.
Highlights: First genetic study comparing different lung cancers with intestinal differentiation Non-colloid compartments of colloid adenocarcinomas are genetically distinct MYC amplification could be a recurrent event in colloid adenocarcinomas In comparison, pulmonary enteric adenocarcinomas have the highest mutational burden mTORC1/2 inhibitors could be potential options for pulmonary enteric adenocarcinoma Abstract: Objectives: We aim to provide a better understanding of the molecular landscape of primary lung adenocarcinomas with intestinal differentiation. Material and Methods: Five invasive mucinous adenocarcinomas (IMA) and seven pulmonary enteric adenocarcinomas (PEAD) were included in this study. Furthermore, we analyzed six pulmonary colloid adenocarcinomas (CAD), including one primary tumor, one metastasis, and two sample pairs consisting of the primary colloid lung tumor and a matching metastasis and an acinar component, respectively. All samples were characterized using immunohistochemistry (TTF-1, CK7, CK20, CDX2, Ki-67, ALK and PD-L1) and a next generation sequencing panel covering 404 cancer-related genes (FoundationOne® gene panel). Results and Conclusion: While Ki-67 expression was comparably low in IMA (range: 8-15%) and in primary CAD (range: 5-8%), we observed considerably higher proliferation rates in the non-colloid tumor compartment (16%) and metastases (72%) from CAD, as well as in the PEAD-group (36-71%). The overall tumor mutational burden was lowest in IMA (2.5 mutations per megabase), intermediate in CAD (5.8 mutations per megabase) and highest in PEAD (16.8 mutations per megabase). KRAS mutations were frequent in all three tumor subtypes, but TP53 mutations were mostly limited to PEAD. While chromosomal alterations were rare in IMA, we discovered MYC amplifications in three of four CAD. Comparing primary and metastatic CAD, we observed the acquisition of multiple mutations and chromosomal alterations. PEAD had a variety of chromosomal alterations, including two cases with RICTOR amplification. PD-L1 expression (20%, 50% and 80% of tumor cells) was limited to three PEAD samples, only. In conclusion, we provide a detailed insight into the molecular alterations across and within the different subtypes of pulmonary adenocarcinomas with intestinal differentiation. From a clinical perspective, we provide data on potential treatment strategies for patients with PEAD, including immunotherapy.